Comparisons Based on Event-related Potentials in Dental Students with Different Levels of Experience Knowledge - Ebihara, Tomoyasu; Aoki, Shinichiro; Doi, Kenji (International Journal of Oral-Medical Sciences, 2017)
The information handling processes for character and tooth recognition tasks were compared between the dental students who had acquired different knowledge levels. The subjects included 20 second-year students who had acquired textbook-based knowledge and 20 fifth-year students who had acquired both textbook-based and experience knowledge though ongoing clinical exercise. The task was to differentiate diagrams depicting a “katakana character” or a “tooth”. The diagrams were randomly presented at a ratio of 2: 8 according to the oddball paradigm. The subjects were instructed to push a button only when a target stimulus was presented. Average waveforms were determined by averaging ERP waveforms derived at Pz for a principal component analysis(PCA).The results showed the same trends in information for character diagrams in both year students; the contribution rates of the PCA component representing pattern matching or attention-orientation as well as working memory update was higher. Similar trends were observed in information for tooth diagrams in terms of a greater percentage of the PCA components represented cognition and decision and behavior performance, but in the fifthyear students P3a that represented attention-orientation was extracted independently.These results indicate similar information in both-year students for the character task,whereas fifth-year students who had acquired experience knowledge appeared to make their decisions based on more effective thinking for the tooth task.